Academic performance study in young athletes from Playas de Castellón Athletics Club - Ana Capdevila Seder; Héctor Bellmunt Villalonga; Carlos Hernando Domingo (Federación Extremeña de Balonmano; University of Extremadura, 2014)
The study analyzed the possible relationship between academic performance of young athletes and some of the variables most used in this field. The sample consisted of 40 athletes Athletics Club Playas de Castellón, between 14 and 16 years, 22 boys and 18 girls. The main variables analyzed were academic performance, study habits, gender, sleep, sedentary leisure, socioeconomic status and dedication to sport. The instruments used were questionnaires CHTE (habits and study skills), PFYTL (physical practice and use of leisure time) and the Questionnaire for parents. The results showed that academic performance was positively correlated with the dedication to sport and negatively with sleep. In addition, the female gender had a higher performance than male.